2002
DOI: 10.1103/physrevlett.89.137005
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Flux Flow due to Heated Electrons in Superconducting Films

Abstract: A flux instability occurs in superconductors at low temperatures, where ee scattering is more rapid than ep, whereby the dissipation significantly elevates the electronic temperature while maintaining a thermal-like distribution function. The reduction in condensate and rise in resistivity produce a non-monotonic current-voltage response. In contrast to the Larkin-Ovchinnikov instability where the vortex shrinks, in this scenario the vortex expands and the quasiparticle population rises. Measurements in Y1Ba2C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
134
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(141 citation statements)
references
References 21 publications
6
134
1
Order By: Relevance
“…From past experience with other films (e.g., Y 1 Ba 2 Cu 3 O 7 on LaAlO 3 ) we found that micron-wide bridges typically have thermal resistances of order R th ∼ 1-10 nK.cm 3 /W at microsecond timescales [1,6,7]. For the present film-substrate combination, complete information about the thermal constants was not available to calculate R th from first principles, but we are able to show by other means that sample heating is not appreciable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From past experience with other films (e.g., Y 1 Ba 2 Cu 3 O 7 on LaAlO 3 ) we found that micron-wide bridges typically have thermal resistances of order R th ∼ 1-10 nK.cm 3 /W at microsecond timescales [1,6,7]. For the present film-substrate combination, complete information about the thermal constants was not available to calculate R th from first principles, but we are able to show by other means that sample heating is not appreciable.…”
Section: Methodsmentioning
confidence: 99%
“…For the present film-substrate combination, complete information about the thermal constants was not available to calculate R th from first principles, but we are able to show by other means that sample heating is not appreciable. Further details of the measurement techniques have been published in a previous review article [7] and other recent papers [1,6]. All measurements were made in zero applied magnetic field and the highest self field of the current (∼ 300 G) is of the order of the lower-critical field H c1 =185 G [8].…”
Section: Methodsmentioning
confidence: 99%
“…This causes an expansion of the vortex core and a drop in viscosity leading to a non-monotonic ("N" shaped) j(E) curve and a consequent instability. Such a hot-electron instability model was developed and experimentally verified by us in our earlier work 9,11 .…”
Section: Introduction and Theorymentioning
confidence: 99%
“…At much higher current densities one may encounter nonlinear effects in the flux flow leading ultimately to the point of instability where a dramatic increase of the measured voltage occurs. 10,11,12,13,14,15 The nonlinear behavior is temperature and magnetic field dependent. Hence, the linear flux flow regime may occur inbetween the two nonlinear regimes, and may not always be well resolved.…”
mentioning
confidence: 99%